2018
DOI: 10.5194/esd-9-797-2018
|View full text |Cite
|
Sign up to set email alerts
|

Hazards of decreasing marine oxygen: the near-term and millennial-scale benefits of meeting the Paris climate targets

Abstract: Abstract. Ocean deoxygenation is recognized as key ecosystem stressor of the future ocean and associated climate-related ocean risks are relevant for current policy decisions. In particular, benefits of reaching the ambitious 1.5 • C warming target mentioned by the Paris Agreement compared to higher temperature targets are of high interest. Here, we model oceanic oxygen, warming and their compound hazard in terms of metabolic conditions on multi-millennial timescales for a range of equilibrium temperature targ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 75 publications
5
36
0
Order By: Relevance
“…The assessment of the performance of a given model version using observational benchmarks has also been actively discussed in the literature (Hoffman et al, 2017;Peng et al, 2014;Kelley et al, 2013;Luo 15 et al, 2012;Blyth et al, 2011;Randerson et al, 2009) and different frameworks have been proposed. Here we employ the Latin Hypercube Sampling (LHS) (McKay et al, 1979) approach, as used successfully in previous studies Battaglia et al, 2016;Steinacher and Joos, 2016;Battaglia and Joos, 2017;Zaehle et al, 2005). It allows simultaneous stratified sampling of a range of parameters, given an appropriate prior parameter distribution, while offering the opportunity to change evaluation metrics a posteriori, thus enabling a sensible incorporation of multiple observational constraints.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The assessment of the performance of a given model version using observational benchmarks has also been actively discussed in the literature (Hoffman et al, 2017;Peng et al, 2014;Kelley et al, 2013;Luo 15 et al, 2012;Blyth et al, 2011;Randerson et al, 2009) and different frameworks have been proposed. Here we employ the Latin Hypercube Sampling (LHS) (McKay et al, 1979) approach, as used successfully in previous studies Battaglia et al, 2016;Steinacher and Joos, 2016;Battaglia and Joos, 2017;Zaehle et al, 2005). It allows simultaneous stratified sampling of a range of parameters, given an appropriate prior parameter distribution, while offering the opportunity to change evaluation metrics a posteriori, thus enabling a sensible incorporation of multiple observational constraints.…”
mentioning
confidence: 99%
“…Transient Land uptake (Inversion) Global land uptake from atmospheric inversion (Boden et al, 2017;Battaglia and Joos, 2017) Transient Land uptake (IPCC) Global land uptake in five periods The modeled total and soil carbon distribution between 1982 and 2005 are compared to a data set based on observations (Carvalhais et al, 2014), regridded to the model resolution. The soil carbon map is divided into low and high latitudes regions in order to avoid potential biases from peat areas with very high soil carbon content.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that global warming can lead to a significant reduction in the amount of oxygen stocked in the ocean [6], in particular by reducing the oxygen solvability and slowing down the ocean upturning and mixing [7]. If this happens, it could have a devastating effect on marine life [8]. More recently, it has been shown that the effect of warming on the total oxygen budget in the ocean can be even worse, as a sufficiently large increase in the water temperature can disrupt the net oxygen production by phytoplankton's photosynthesis [15,17].…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…Somewhat less publicized in the media, but perhaps even more dangerous is the observed decrease in the concentration of dissolved oxygen in the ocean [6]. It is predicted that in the worst case scenario, the amount of ocean oxygen could fall almost twice [7], which would lead to disastrous consequences for the ocean ecosystems by suffocating most of marine life [8].…”
Section: Introductionmentioning
confidence: 99%